Algebra & Trigonometry with Analytic Geometry
13th Edition
ISBN: 9781133382119
Author: Swokowski
Publisher: Cengage
expand_more
expand_more
format_list_bulleted
Question
![## Fibonacci Sequence
The Fibonacci sequence \( y_0, y_1, y_2, \ldots \) starts with \( y_0 = 0 \), \( y_1 = 1 \), and for \( t = 2, 3, \ldots \),
\[
y_t = y_{t-1} + y_{t-2},
\]
i.e., the sum of the previous two entries.
### Tasks:
(a) **Linear Dynamical System Representation**
- Express this as a time-invariant linear dynamical system with state \( x_t = (y_t, y_{t-1}) \) and output \( y_t \), for \( t = 1, 2, \ldots \). That is, find \( A \) and \( C \), where
\[
x_{t+1} = Ax_t \quad \text{and} \quad y_t = Cx_t.
\]
(b) **MATLAB Simulation**
- Use your matrix expression above and MATLAB to compute and plot the Fibonacci sequence \( y_t \) for \( t = 0, \ldots, 20 \).
(c) **Modified Fibonacci Sequence**
- Using MATLAB, simulate a modified Fibonacci sequence \( z_0, z_1, z_2, \ldots \), which starts with the same values \( z_0 = 0 \) and \( z_1 = 1 \), but for \( t = 2, 3, \ldots \),
\[
z_t = z_{t-1} - z_{t-2},
\]
i.e., the difference of the two previous values. Plot this sequence \( z_t \) for \( t = 0, \ldots, 20 \).](https://content.bartleby.com/qna-images/question/1da88d38-e18c-40f1-9bb8-69bad3269ec7/0cc6d8ac-9561-4798-96fd-5aa31c2695d7/b2a3hu_thumbnail.png)
Transcribed Image Text:## Fibonacci Sequence
The Fibonacci sequence \( y_0, y_1, y_2, \ldots \) starts with \( y_0 = 0 \), \( y_1 = 1 \), and for \( t = 2, 3, \ldots \),
\[
y_t = y_{t-1} + y_{t-2},
\]
i.e., the sum of the previous two entries.
### Tasks:
(a) **Linear Dynamical System Representation**
- Express this as a time-invariant linear dynamical system with state \( x_t = (y_t, y_{t-1}) \) and output \( y_t \), for \( t = 1, 2, \ldots \). That is, find \( A \) and \( C \), where
\[
x_{t+1} = Ax_t \quad \text{and} \quad y_t = Cx_t.
\]
(b) **MATLAB Simulation**
- Use your matrix expression above and MATLAB to compute and plot the Fibonacci sequence \( y_t \) for \( t = 0, \ldots, 20 \).
(c) **Modified Fibonacci Sequence**
- Using MATLAB, simulate a modified Fibonacci sequence \( z_0, z_1, z_2, \ldots \), which starts with the same values \( z_0 = 0 \) and \( z_1 = 1 \), but for \( t = 2, 3, \ldots \),
\[
z_t = z_{t-1} - z_{t-2},
\]
i.e., the difference of the two previous values. Plot this sequence \( z_t \) for \( t = 0, \ldots, 20 \).
Expert Solution
![Check Mark](/static/check-mark.png)
This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
This is a popular solution
Trending nowThis is a popular solution!
Step by stepSolved in 5 steps with 41 images
![Blurred answer](/static/blurred-answer.jpg)
Knowledge Booster
Similar questions
- Find the third term of the sequence {2n^2/3^n-1}from n=1 to ∞arrow_forwardFind the limit of the sequencearrow_forward. Let $n \in \mathrm{N}^{*}$ and the equation:$$C_{2 n+1}^{1} x^{n}-C_{2 n+1}^{3} x^{n-1}+C_{2 n+1}^{5} x^{n-2}-\ldots+(-1)^{k} C_{2 n+1}^{2 k+1} x^{n-k}+\ldots+(-1)^{n} C_{2 n+1}^{2 n+1}=0$$Show that:a) the equation admits as roots the numbers::$\mathrm{x}_{\mathrm{k}}=\operatorname{ctg}^{2} \frac{k \pi}{2 n+1}$, for every $k \in\{1.2, \ldots . n\}$ b) $\frac{\pi^{2} n(2 n-1)}{3(2 n+1)^{2}}<\sum_{k=1}^{n} \frac{1}{k^{2}}<\frac{2 \pi^{2} n(n+1)}{3(2 n+1)^{2}}$ c) $\frac{\pi^{4} n(2 n-1)\left(4 n^{2}+10 n-9\right)}{45(2 n+1)^{4}}<\sum_{k=1}^{n} \frac{1}{k^{4}}<\frac{8 \pi^{4} n(n+1)\left(n^{2}+n+3\right)}{45(2 n+1)^{4}}$ d) $\lim _{n \rightarrow \infty} \sum_{k=1}^{n} \frac{1}{k^{2}}=\frac{\pi^{2}}{6}$ e) $\lim _{n \rightarrow \infty} \sum_{k=1}^{n} \frac{1}{k^{4}}=\frac{\pi^{4}}{4}$ Please check the attached picture for details. I need complete solution with explanation please. the all fifth subpoints are for the same problem and they are conected between them, but if…arrow_forward
- The generating function of the sequence 5,5,5,5,5 is 1-x5 O (1-x) 5 1-5x° O (1-x) 1-125x5 (1-x) 1-3125x5 (1-x)arrow_forward{1 -} The sequence is (i) 0 (ii) 1 (iii) None of thesearrow_forwardA sequence {a^n} of real numbers is defined recursively by a_1=2 for n ≥ 2, a_n=(2+1∙a_1^2+2∙a_2^2+⋯+(n-1) a_(n-1)^2)/n Determine a_(2,) a_3, and a_4. Show all work. Clearly, a_n is a rational number for each n ϵ N. Based on the information in a), however, what conjecture does this suggest?arrow_forward
arrow_back_ios
SEE MORE QUESTIONS
arrow_forward_ios
Recommended textbooks for you
- Algebra & Trigonometry with Analytic GeometryAlgebraISBN:9781133382119Author:SwokowskiPublisher:Cengage
Algebra & Trigonometry with Analytic Geometry
Algebra
ISBN:9781133382119
Author:Swokowski
Publisher:Cengage